2003
DOI: 10.1523/jneurosci.23-13-05846.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Trophic Role of Oligodendrocytes in the Basal Forebrain

Abstract: Traditionally, the primary function of oligodendrocytes (OLGs) in the CNS has been considered to be myelination. Here, we investigated whether OLGs may play a trophic role, particularly during development. Neurotrophin expression was assessed in postnatal day 7 basal forebrain (BF) OLGs, using in situ hybridization and detection of myelin basic protein. Nerve growth factor, brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3) mRNAs were revealed in OLGs in vivo and in culture. To determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 50 publications
3
93
0
1
Order By: Relevance
“…For example, they have been shown to regulate transmitter release, synaptic size and stability, and to modulate shortand long-term synaptic plasticity (56)(57)(58)(59). Although neurons have long been viewed as the primary source of BDNF in the central nervous system, recent studies have reported BDNF expression in both oligodendrocytes and astrocytes (60)(61)(62). As these central glia also express erbB receptors, it is important to consider the possibility that erbB signaling regulates neurotrophin expression in these cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they have been shown to regulate transmitter release, synaptic size and stability, and to modulate shortand long-term synaptic plasticity (56)(57)(58)(59). Although neurons have long been viewed as the primary source of BDNF in the central nervous system, recent studies have reported BDNF expression in both oligodendrocytes and astrocytes (60)(61)(62). As these central glia also express erbB receptors, it is important to consider the possibility that erbB signaling regulates neurotrophin expression in these cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus oligodendrocytes in the corpus callosum (Dai et al, 2003) express the neurotrophin and cultured as well in vivo astrocytes are known to express the neurotrophin (Dougherty et al, 2000;Wu et al, 2004;Jean et al, 2008). Interestingly, the nonastrocyte derived BDNF appears to dominate overall protein levels of BDNF seen in the unlesioned control since this population is reduced following cuprizone, coincident with a decrease in BDNF as defined by Western blot.…”
Section: Effects Of Other Astrocyte-derived Molecules Following a Demmentioning
confidence: 99%
“…Astrocytes also generate complement proteins that modulate synaptic pruning (78). Oligodendrocytes secrete trophic factors that influence the survival and function of neighboring neurons (79), enhance the number of functional synapses between neurons, and can directly regulate neuronal activity (80). Thus, impaired maturation of oligodendroglia may contribute to the impaired maturation of the developing gray matter and vice versa.…”
Section: Mechanisms Of Maturational Impairmentmentioning
confidence: 99%